Fracture toughness and fatigue resistance of quenched and tempered steels with microstructures deriving from a slant quench. Consequences on technical standards - D. Firrao; P. Matteis (Fracture and Structural Integrity)
Mechanical components fabbricated with quenched and tempered steels, exhibiting mixed microstructures as derived from slant quench conditions, are frequently encountered in the industrial practice, owing to a tendency to employ quite low alloy steels or due to quite large sections. The low notch strength of mixed microstructure steel samples was already emphasized in the 1950s; yet, it has never been investigated again. Also, technical standards have not addressed the risk deriving from the use of steel components with mixed microstructures. When pearlite and ferrite are present alongside tempered martensite and bainite, the fracture toughness of steel pieces diminishes to very dangerous levels. Results of an experimental program on the fracture toughness of plastic mould steels are reported, singling out microstructure mixtures with too a low toughness. In addition, the fatigue crack propagation rate is adversely affected by inhomogeneous metallographic structures. It is inferred that experimental results and ensuing considerations should be taken into account when formulating technical norms.